2012
DOI: 10.4236/as.2012.34073
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming seasonality in the tropics by growing tomato (<i>Lycopersicon esculentum Mill.</i>) varieties under cooled conditions

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The results are in accordance with early findings in which eleven tomato varieties tested for their adaptability and got variation in fruit cluster -1 among varieties [22]. Likewise another study also found variation in number of fruit -1 among different tomato varieties [23]. The means followed by the same letter within the same column are not significantly different at 5% level of significance…”
Section: Number Of Clusters Per Plantsupporting
confidence: 91%
“…The results are in accordance with early findings in which eleven tomato varieties tested for their adaptability and got variation in fruit cluster -1 among varieties [22]. Likewise another study also found variation in number of fruit -1 among different tomato varieties [23]. The means followed by the same letter within the same column are not significantly different at 5% level of significance…”
Section: Number Of Clusters Per Plantsupporting
confidence: 91%
“…Even with the inclusion of the irrigation scenario in the current model, large areas were observed as unsuitable in North Africa (excluding the Mediterranean) due to heat and dry stress. In summer, due to high temperatures, a shortage of tomatoes is common in many parts of the African continent (El-Amin & Ali 2012). The CS GCM predicts that dry and heat stress will increase drastically in 2050 and 2100 in Africa and India.…”
Section: Discussionmentioning
confidence: 99%
“…The tomato plant prefers warmer weather with the optimum range of air temperature for normal growth and fruit set between 20 and 30 °C (Heuvelink 2005; Jones 2007); however, the tomato plant can survive in a range between 10 and 35 °C (Heuvelink 2005; El-Amin & Ali 2012; Attoh et al 2014). Temperatures below 10 °C cause inhibition of vegetative development and a reduction of fruit set and ripening, while air temperatures above 35 °C cause a reduction of fruit set and the inhibition of normal fruit colour development (Heuvelink 2005; Jones 2007).…”
Section: Methodsmentioning
confidence: 99%